Assessment of the prozone effect in malaria rapid diagnostic tests - Gillet Philippe; Mori Marcella; Van Esbroeck Marjan; Ende Jef; Jacobs Jan (Malaria Journal, 2009)
Abstract Background The prozone effect (or high doses-hook phenomenon) consists of false-negative or false-low results in immunological tests, due to an excess of either antigens or antibodies. Although frequently cited as a cause of false-negative results in malaria rapid diagnostic tests (RDTs), especially at high parasite densities of Plasmodium falciparum, it has been poorly documented. In this study, a panel of malaria RDTs was challenged with clinical samples with P. falciparum hyperparasitaemia (> 5% infected red blood cells). Methods Twenty-two RDT brands were tested with seven samples, both undiluted and upon 10 ×, 50 × and 100 × dilutions in NaCl 0.9%. The P. falciparum targets included histidine-rich protein-2 (HRP-2, n = 17) and P. falciparum-specific parasite lactate dehydrogenase (Pf-pLDH, n = 5). Test lines intensities were recorded in the following categories: negative, faint, weak, medium or strong. The prozone effect was defined as an increase in test line intensity of at least one category after dilution, if observed upon duplicate testing and by two readers. Results Sixteen of the 17 HRP-2 based RDTs were affected by prozone: the prozone effect was observed in at least one RDT sample/brand combination for 16/17 HRP-2 based RDTs in 6/7 samples, but not for any of the Pf-pLDH tests. The HRP-2 line intensities of the undiluted sample/brand combinations with prozone effect (n = 51) included a single negative (1.9%) and 29 faint and weak readings (56.9%). The other target lens (P. vivax-pLDH, pan-specific pLDH and aldolase) did not show a prozone effect. Conclusion This study confirms the prozone effect as a cause of false-negative HRP-2 RDTs in samples with hyperparasitaemia.